Levers of Control and Managerial Performance: The Importance of Belief Systems - Ancella Anitawati Hermawan; Emil Bachtiar; Panggah Tri Wicaksono; Nia Pramita Sari (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Belief systems, which are one of the four levers of control, play a vital role in an organization. This study is primarily aimed at examining the effects of belief systems on managerial performance. Since the four levers of control jointly function in management control systems, we extend our study by investigating whether the contingent-fit between strategic risk, strategic uncertainty, and the other three levers of control (i.e., boundary systems, diagnostic control, and interactive control) strengthens the association between belief systems and managerial performance. A survey questionnaire was distributed to the upper-level management of various companies or strategic business units in Indonesia during the fourth quarter of 2017, resulting in 81 respondents. Hypotheses testing were conducted using the OLS regression model. This research found that belief systems are positively associated with managerial performance, indicating that the implementation of effective belief systems leads to higher managerial performance. This study also found that the contingent-fit between strategic risk, strategic uncertainty, and the other three levers of control does not have any effect on how belief systems are positively associated with managerial performance. This finding indicates that although management does not adopt a fit combination between its level of strategic risk and strategic uncertainty and the boundary systems, diagnostic control, and interactive control, it can still achieve good performance as long as strong belief systems are implemented. These findings confirm the critical role of belief systems in the levers of control. Thus, management needs to ensure the establishment of more effective belief systems if the company or business unit wants to produce optimal performance.